2002
DOI: 10.1139/h02-034
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Interchangeability of and Oxygen Uptake Efficiency Slope

Abstract: A reliable submaximal test for assessing cardiorespiratory function would be of interest in clinical practice. Baba et al. (1996) proposed the oxygen uptake efficiency slope (OUES) derived from the relation between oxygen uptake (VO2 [ml x min (-1) x kg (-1)]) and minute ventilation (VE [L x min (-1)]) during incremental exercise. We evaluated the validity of OUES by comparing maximal oxygen uptake (VO2MAX) predicted from OUES to measured VO2MAX in 50 healthy males who performed a maximal treadmill test. They … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
32
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 23 publications
6
32
0
Order By: Relevance
“…In agreement with previous studies (Baba et al 1999a;Hollenberg and Tager 2000;Pichon et al 2002;Mourot et al 2004), no significant difference was detected between OUES100 (i.e. OUES calculated based on 100% of exercise data-points) and OUES90 or OUES75 (i.e.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In agreement with previous studies (Baba et al 1999a;Hollenberg and Tager 2000;Pichon et al 2002;Mourot et al 2004), no significant difference was detected between OUES100 (i.e. OUES calculated based on 100% of exercise data-points) and OUES90 or OUES75 (i.e.…”
Section: Discussionsupporting
confidence: 93%
“…As demonstrated by others for traditional OUES values (Baba et al 1999b;Hollenberg and Tager 2000;Pichon et al 2002;Mourot et al 2004;Davies et al 2006), OUES80% res and 60% res were highly correlated with indexes of aerobic exercise capability (i.e. _ VO 2peak and VT).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Previously published evaluations of the oxygen uptake efficiency slope have been limited to healthy volunteers [19][20][21] and patients with cardiac disease [7-9, 22, 23], and test-retest reliability has only been reported in healthy adults. Van Laethem et al [19] studied 18 healthy subjects, performing two separate tests.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the correlation between the two indices OUES and VO 2max in these patients was R = 0.71. 19 Other scientific evidence on the fat children 20,21 or normal weight children 22,23 also pointed out that the OUES can be used in the different ages to assess cardiorespiratory fitness level. Marinov's and Kostianev 20 report on the influence of body composition on OUES showed that OUES In the obese children is lower than that in non-obese counterparts.…”
Section: Introductionmentioning
confidence: 99%